Relationship between Czech Parent and Child Pedometer-assessed Weekday and Weekend Physical Activity and Screen Time - Sigmund, Erik; Sigmundová, Dagmar; Baďura, Petr; Voráčová, Jaroslava (Central European journal of public health, 2015)
AIM: Uncovering the influences of parents' behaviour on their children's physical activity provides an insight into the lifestyle of families and development of effective family-based interventions. The aim of this study was to determine the relationship between parents' behaviour (step count (SC) and screen time (ST)) and children's SC on weekdays and at weekends. METHODS: The participants (388 parents aged 35-45 and their 485 children aged 9-12) were randomly recruited from 21 Czech government funded primary schools. The participants recorded SC and ST duration for seven consecutive days (≥ 10 h/day) during April-May and September-October 2013. The associations between parents' behaviour (SC and ST) and children's SC were estimated using general linear regression separately for weekdays and weekends. Each 1,000 SC increase in mothers' (fathers') SC/weekday was associated with an extra 261 SC/day in their daughters and 413 (244) SC/day in their sons. RESULTS: Each 1,000 SC increase in mothers' (fathers') SC/weekend day was associated with an extra 523 (386) SC/day in their daughters and 508 (435) SC/day in their sons. A reduction in mothers' ST by 30 minutes per weekend day was associated with an extra 494 SC/day in their daughters and 467 SC/day in their sons. CONCLUSIONS: This study reveals a quantifiable relationship between parent-child SC/day and mothers' ST and children's SC at weekends. Weekend days are more suitable for the implementation of family-based interventions.
Keywords: Accelerometry; dospělí; Female; dítě; akcelerometrie; Television; Adult; ženské pohlaví; vztahy mezi rodiči a dětmi; Life Style; životní styl; pohybová aktivita; lidé; Yamax pedometer; step count; Computers; weekdays and weekends; daughters and sons; Male; televize; Czech Republic; Parent-Child Relations; Česká republika; Motor Activity; lidé středního věku; Child; počítače; mužské pohlaví; screen time; Middle Aged; Humans